FORMATION OF THE NEW "UNPRODUCTIVE CLASSES" IN A DIGITAL SOCIETY - Firsov , M.; Chernikova, A. (EurasianUnionScientists, 2021)
The digital society, which has undergone rapid development in the last decade in the Russian Federation, has introduced new trends in the "formation of problems" not only among the productive, but also unproductive segments of the population. So, the new "unproductive classes" in the Russian Federation are being formed in a situation of new historical conditions, the coordinates of which extend to the entire global world and it can be said with all certainty that the problems of Russian society are determined, among other things, by the trends of the "information world community", a part of which today it is.